استكشاف الفهم الخلقي عن تعليم اللغة العربية وتعلمها في معهد أم كلثوم الإسلامي كونونج ستولي - Muhammad Habib Ismail Ramadhan; Achyar Zein (Lembaga Yasin AlSys, 2025)
This study aims to describe the perspectives and practices of Arabic language teachers concerning teaching ethics at Pondok Pesantren Ummi Kalsum Gunungsitoli. A qualitative approach with a descriptive-analytical method was employed. Data collection techniques included observation, in-depth interviews, and documentation to obtain a comprehensive understanding of the implementation of ethical principles in the Arabic language teaching process. The findings reveal that the understanding and application of ethics in Arabic language instruction play a crucial role in shaping positive behavior among both educators and students. Teaching ethics are practiced through role modeling, discipline, and interactions grounded in moral and Islamic values. Teachers actively encourage students to enhance their learning ethics as part of character and moral development. This study focuses on aspects such as students' moral formation, faith reinforcement, and mastery of Arabic and religious sciences, which are central to pesantren education. The implications suggest that ethics-based Arabic language instruction not only strengthens linguistic competence but also supports character education goals within the pesantren context.